In vitro neutralization of Eachis carinatus and Naja naja venom by Canthium parviflorum and its GC-MS analysis (Bangladesh Journal of Pharmacology, 2016)
Canthium parviflorum is used in the traditional therapy to treat snakebite victims. In the present study, partially purified methanol root extract of C. parviflorum was used for the neutralization of Eachis carinatus and Naja naja venom. The extract inhibited in vitro phosphomonoesterase, phosphodiesterase, acetylcholinesterase, hyaluronidase, protease, phospholipase A2 and 5nucleotidase activities of both venoms. One of the promising band exhibited neutralization of all the in vitro enzyme activities and was further subjected to GC-MS analysis which revealed the presence of eight active phytocompounds. These phytochemicals might be responsible for in vitro enzyme neutralization. Methanol extract possesses potent active phytochemicals against the site specific toxins and hydrolytic enzymes analyzed.Video Clip of Methodology:Phospholipase A2 assay: 1 min 36 sec  Full Screen   Alternative